Adaptation of a Sexual Violence Measuring Tool to Classify the Risk of Convicts Who Perpetrate Sexual Violence - Rachmayanthy .; Maki Zaenudin S; Iman Santoso; Ali Muhammad; Imaduddin Hamzah (Polteknik Ilmu Pemasyarakatan, 2023)
This study aims to develop a risk assessment tool for sexual violence recidivism in incarcerated individuals in Indonesia, considering both static and dynamic factors. Data analysis showed a strong positive correlation between recidivism and